Cover Picture: Hydrogen‐Bonded Metal–Nucleobase Frameworks for Efficient Separation of Xenon and Krypton (Angew. Chem. Int. Ed. 11/2022). Issue 11 (14th February 2022) - Liu, Ying; Wu, Hui; Guo, Lidong; Zhou, Wei; Zhang, Zhiguo; Yang, Qiwei; Yang, Yiwen; Ren, Qilong; Bao, Zongbi
Abstract : Hydrogen‐bonded frameworks self‐assembled from metal–nucleobase complexes and hexafluoro anions are reported by Wei Zhou, Zongbi Bao et al. in their Research Article (e202117609) . Amino‐rich ligands provide multiple H‐bonding sites to stabilize the frameworks. In the confined channels, the electron‐rich anions combined with the electron‐deficient purine rings generate a micro‐electric field to polarize and lock Xe atoms, thus achieving highly efficient Xe/Kr separation under ambient conditions.